2021
DOI: 10.7554/elife.65215
|View full text |Cite
|
Sign up to set email alerts
|

Miro1-dependent mitochondrial dynamics in parvalbumin interneurons

Abstract: The spatiotemporal distribution of mitochondria is crucial for precise ATP provision and calcium buffering required to support neuronal signaling. Fast-spiking GABAergic interneurons expressing parvalbumin (PV) have a high mitochondrial content reflecting their large energy utilization. The importance for correct trafficking and precise mitochondrial positioning remains poorly elucidated in inhibitory neurons. Miro1 is a Ca²⁺-sensing adaptor protein that links mitochondria to the trafficking apparatus, for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…The emerging role of Miro1 in the development and progression of diseases, particularly neurological disorders, underscores the need for new methods and tools to study this protein in detail at the molecular level (Fatiga et al, 2021;Kassab et al, 2021;Kontou et al, 2021;López-Doménech et al, 2021;Nguyen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging role of Miro1 in the development and progression of diseases, particularly neurological disorders, underscores the need for new methods and tools to study this protein in detail at the molecular level (Fatiga et al, 2021;Kassab et al, 2021;Kontou et al, 2021;López-Doménech et al, 2021;Nguyen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The emerging role of Miro1 in the development and progression of diseases, particularly neurological disorders, underscores the need for new methods and tools to study this protein in detail at the molecular level ( Fatiga et al, 2021 ; Kassab et al, 2021 ; Kontou et al, 2021 ; López‐Doménech et al, 2021 ; Nguyen et al, 2021 ). Currently, most studies rely on ectopic expression of genetically modified (tagged) Miro1 ( Kanfer et al, 2015 ; Castro et al, 2018 ; Nemani et al, 2018 ; Fatiga et al, 2021 ) which previously has been shown to affect mitochondrial morphology and transport in living cells ( Fransson et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 ) is in keeping with previous studies in axons of other cell types and different models of demyelination 7 , 8 , 11 , suggesting its toxicity does not play a role in the present analysis. To determine the features of motility, Ca 2+ buffering, anatomical properties of size and shape as well as the distribution of the mitochondria in PV + interneurons we used two-photon and confocal microscopy together with 3D EM data, which have been used previously to study mitochondria 7 , 9 , 35 , 50 , 77 . Confocal imaging has the advantage of allowing the mapping of mitochondria in large parts of single cells from multiple animals and distinct genetically modified mice but with the tradeoff of a lower spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…If in PV + interneurons newly formed myelin sheaths attract mitochondria this could represent a glial mechanism to strengthen axonal pathways and promote specific circuits of inhibitory transmission. Both myelination and mitochondrial distribution in PV + interneurons are known to be important for gamma oscillations, indicating they may represent converging pathways that shape PV + interneuron inhibitory functions 22 , 35 . More research will be necessary to test this hypothesis, by for instance using longitudinal mitochondrial imaging during myelin development or activity-induced myelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation